PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN KINERJA KEUANGAN PADA HARGA SAHAM - Safira, Zhara; Riduwan, Akhmad (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purposes of this research are: (a) to find out the influence of the disclosure of Corporate Social Responsibility on the stock price; (b) to find out the influence of financial performance on the stock price. The samples are manufacturing companies which are listed in Indonesia Stock Exchange (IDX) during the 2010-2013 periods; the samples are 37 companies which have been selected by using purposive sampling. The multiple linear regressions analysis is used as analysis technique. The result of this research shows that i.e.: (a) the disclosure of Corporate Social Responsibility does not have any significant influence to the stock price. The absence of significant influence means that the public does not notice the information which has been delivered by the company about the concern of the company to the social problems, so that it does not have any influence to the demand of the investors request of the company stock, finally it does not give any significant influence to the stock price; (b) Return On Assets has positive influence to the stock price. A good development on return on assets will add the investorsâ belief to the magnitude of the profit that can be provided by the company. When the demand of the investor to the company stock is large, this can have influence to the enhancement of stock price; (c) the return on equity has positive influence to the stock price. The value of return on equity is high it is an encouraging matter for the investors when the profit which is provided for the investors is getting larger, the investors will be interested in purchasing the company stock. If the demand of the investors to the company stock is quite large, it will have influence to the enhancement of the stock price.Keywords: Corporate Social Responsibility, Return on Assets, Return On Equity and Stock Price.